Bachelor programme in Urban and Regional Planning (Faculty of Architecture Yıldız Technical University) - Dabović, Tijana; Perić, Ana; Fikfak, Alenka (AESOP, 2023)
The BSc in Urban and Regional Planning delivered at the Yildiz Technical University is distinctive in its focus on theoretical and methodological courses, interdisciplinarity and regional science. It brings together the following aspects of quality in planning education: Programme Curriculum and Identity - A blend of substantive planning courses and courses focused on communicative and strategic spatial planning constitute the three main pillars of the curriculum: knowledge, skills for professional competencies, and values and ethics, making the latter a crucial component of the curriculum. - Focus on contemporary research areas in urban and regional planning enable students to understand, research and apply their knowledge, skills and attitudes to solve complex problems and recognise and enable future opportunities in cities and regions. - Progression from mainly compulsory courses in the 1st year towards more elective ones on the final year stimulates the progression in student’s responsibility for their education and future professional engagement in urban and regional planning. - An excellent balance and exposure to theoretical, methodological and policy-based courses delivered by a highly qualified teaching team engaged in public services, visiting professors from a well-established global network, stakeholders and practitioners foster the intentional distinctiveness of the programme to integrate planning theory with practice while safeguarding professional ethics.
Faculty of Architecture Yıldız Technical University 41.055306882047056, 29.01058049385181 https://ror.org/0547yzj13
Keywords: strategic spatial planning; policy-based courses; Turkey